Download presentation

Presentation is loading. Please wait.

Published byDennis Simmons Modified over 7 years ago

1
Substitution Method September 9, 2014 Page 14-15 in Notes

2
Warm-Up (page 14) What is an equation? Which of the following equations is linear? – A. 2x + y = 8 – B. 2x 2 + 4x – 3 = 7 What is a linear equation?

3
Solving Systems Using Substitution Title of Notes – pg. 15

4
Essential Question How do I solve systems of linear equations using the substitution method?

5
System of Linear Equations Definition: a set of two or more equations with the same variables Example: 2x + y = 5 5x – 3y = 8

6
Solving Systems of Equations One method we use to solve systems of equations algebraically is called the substitution method. The solution to a system of equations is the ordered pair (x, y) that makes both equations true. It is also the point on the graph where the two lines intersect.

7
Substitution Steps 1.Isolate the “easiest” variable in either equation. 2.Substitute that variable in the other equation and solve for the remaining variable. 3.Substitute this value into the starting equation and solve for your first variable to find the rest of your ordered pair. 4.Check your point in both original equations.

8
Example 1: Solve the system of equations by substitution. x – 2y = 5solution: _______ 4x + 3y = 9 1x = 2y + 5 (Step 1) 4(2y + 5) + 3y = 9 (Step 2) 8y + 20 + 3y = 9 11y + 20 = 9 11y = -11 y = -1 x – 2(-1) = 5 (Step 3) x + 2 = 5 x = 3 So, the solution to the system is (3, -1). Check:(Step 4) x – 2y = 5 4x + 3y = 9 (3) – 2(-1) = 54(3) + 3(-1) = 9 3 + 2 = 5 12 – 3 = 9 5 = 5 9 = 9 (3, -1)

9
3x + y = 19solution: _______ 3x – 2y = 25 Example 2: Solve the system of equations by substitution. y = -3x + 19 (Step 1) 3x – 2(-3x+19) = 25 (Step 2) 3x + 6x – 38 = 25 9x – 38 = 25 9x = 63 x = 7 3(7) + y = 19 (Step 3) 21 + y = 19 y = -2 So, the solution to the system is (7, -2). Check:(Step 4) 3x + y = 19 3x – 2y = 25 3(7) + (-2) = 19 3(7) – 2(-2) = 25 21 – 2 = 19 21 + 4 = 25 19 = 19 25 = 25 (7, -2)

10
Example 3: Solve the system of equations by substitution. 3x = y – 4 (Step 1) 3x + 4 = y 2x + 2y = 8solution: _______ 3x – y = -4 2x + 2(3x + 4) = 8 (Step 2) 2x + 6x + 8 = 8 8x + 8 = 8 8x = 0 x = 0 3(0) – y = -4 (Step 3) -y = -4 y = 4 So, the solution to the system is (0, 4). Check:(Step 4) 2x + 2y = 8 3x – y = -4 3(0) + 2(4) = 8 3(0) – (4) = -4 0 + 8 = 8 0 – 4 = -4 8 = 8 -4 = -4 (0, 4)

11
Practice: On Your Own Paper 1.y = 2x + 15 y = x + 1 2.y = 6 x + 6y = 12 3.x = -6 2x – 3y = 7 4. x – y = 2 4x – 3y = 8 5. x + 2y = -9 3x + 2y = -7 6. 23x + 11y = 1 -2x – y = 0 7. 3x + y = -20 2x – 7y = 2 8. y + 3x = 9 4x + 2y = 17

12
Reflection What did all the problems we looked at today have in common that made it easy to use the substitution method for solving?

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google